Who takes the cake? the heterogeneous effect of European Central Bank accommodative monetary policy across income classes - Bárcena-Martín, Elena María; Martín-Fuentes, Natalia; Pérez-Moreno, Salvador Jesús (Wiley, 2025)
This work provides evidence of the heterogeneous effects of the ECB's monetary policy across income classes. In particular, this investigation focuses on the labor market channel. Based on EU-SILC data, we estimate country-specific structural vector autoregressions (SVAR) models to analyze the impact of the expansionary monetary policy shocks over the 2006–2019 period. The results suggest that monetary easing helped decrease unemployment rates for lower- and middle-income classes, to a larger extent for the former. This differential impact is accounted for a stronger improvement in job finding rates for classes located at the bottom of the income distribution. Conversely, the employment status of the upper class remained largely unaffected. The analysis identifies a positive impact of expansionary monetary policy on real labor income, which seems to have mostly benefitted the upper class. Overall, our results suggest that expansionary monetary policy helped decrease labor income inequality by exerting a stronger positive impact on lower-income households.
Keywords: Banco Central Europeo - Política monetaria - 2006-2019; Monetary policy; Income inequality; Income class; Structural vector autoregressions (SVARs); Euro area